Analisis Penempatan Pegawai Pada Kantor Kecamatan Sebulu Di Kabupaten Kutai Kartanegara - Yuliana Yuliana; Joko Sabtohadi; Rahim Abdullah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract:Human resources which are needed is cost factor due to central to providing services in an organization .Any methods and its aims the organization was created based on the range of vision for the benefit of man and in the implementation of the mission is managed by human beings .Be a man of the main factor of a strategic part of all activities of the organization .The purpose of this research is to know the deployment of an officer at offices of head of subdistricts sebulu in Kutai Kartanegara regency. Then the kind of research that is used is identification descriptive of by the use of of a quantitative approach where is trying in giving a snapshot of the outline or explanation of the an accurate assessment of the areas that can be analyzed in terms of interprestasy and a detailed explanation of existing data shows that in an unsystematic manner based on obyektivitas which appeared to be or as they always have so as to give a picture in on totally objective criteria about the actual state of things of an object that is analyzed in terms of .The results of the study viewed from the side of dimensions expertise be on a level either by the percentage 78,05% and the average score 3.90 dimensions skills are on a level either by the percentage 63,03% and the average score 62,59% dimensions the level of education be on a level either by the percentage 72,22% the average score 3,61 dimensions physically be on a level either by the percentage 62,34% and the average score 3,12 and dimension experience of being on a level either by the percentage 76,22% and the average score 3,81.All are at intervals class good. Keywords: Analysis of Employee Placement